Investigation of injury severity level in truck-related crashes at school zones using mixed generalized ordered models - Junhan Cho; Sungjun Lee; Juneyoung Park (PLoS ONE, 2025)
The number of truck registrations is steadily increasing in Korea. The proportion of truck deaths compared to the total number of traffic crashes was 23.9%, which is significantly higher than that of other vehicles. In the field of traffic safety, the Children’s Safety Measures Policy by government aims to enhance the safety of children’s commuting routes by expanding school zones. Nonetheless, truck crashes continue to occur in school zones. Therefore, this study analyzed the factors that affect the severity of truck traffic crashes in school zones in order to contribute to safety improvements. In the study, a distinction is made between various levels of severity to determine the factors that contribute to each level. The generalized ordered models were applied to investigate injury severity levels. Moreover, in order to account for heterogeneity issue, the mixed-effects models with random parameters were used for the analysis. These models were constructed using data collected from school zones over a period of recent ten years. The results showed that crashes occurred at night and on the weekend, as well as human factors such as the age of the victim and the gender of the offender, the types of vehicles involved, and the road type, have been identified as important factors contributing to crash severity. By considering the factors that contribute to truck crashes in school zones, it is anticipated that road safety can be enhanced.